LABORATORY BIOMARKERS FOR BRAIN DAMAGE IN DIABETES MELLITUS - YU.V. BYKOV1,2; A.A. MURAVYOVA (Avicenna Tajik State Medical University, 2023)
Objective: This review outlines the literature data on the main laboratory biomarkers of brain damage in diabetes mellitus (DM) type I and II. Neurospecific proteins: S-100 protein, neurospecific enolase, glial fibrillar acidic protein, myelin basic protein, and brain-derived neurotrophic factor (BDNF) are considered specific markers of cerebral dysfunction in DM. Emphasis is placed on pro-inflammatory cytokines (IL-1, IL-6, tumor necrosis factor-α, C-reactive protein), as blood biomarkers, the increase of which indicates brain damage in DM type I and II. High concentrations of adipokines, inflammatory mediators of adipose tissue, are a reliable laboratory sign of brain damage in this endocrinopathy. Advanced glycation end products (AGEs), as pathogenic metabolites of oxidative stress (OS), detected in blood in high concentration, can act as indicators of cognitive deficit in DM. Increased concentration of autoantibodies to some neuroreceptors (dopamine, glutamate) may serve as specific laboratory biomarkers of brain damage in DM type I. Further searches of new laboratory biomarkers of brain dysfunction are needed in order to improve the diagnosis of cerebral insufficiency in DM